A comparative study of the records management practices in selected public tertiary level referral hospitals in Manila and Quezon City - Cero, Christine Joyce M.; Aquino, Aurora (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2005)
The study focused on the overall compliance to the Department of Health Hospital Medical Records Management Manual of three of the largest tertiary level referral hospitals in the Philippines, namely the East Avenue Medical Center, the San Lazaro Hospital and the University of the Philippines - Philippine General Hospital. This was done in order to determine whether or not some of the primary medical records management given by the Department of Health.
In order to obtain the required data for the analysis of the medical records management of the respondent hospitals, ocular inspections of the actual medical records storage facilities and interviews with the medical records officers and staff of the respondent medical records units were conducted.
During the course of the study, it was found that, generally, the respondent hospitals adhered to the prescribed medical records management guidelines issued by the Department of Health (DOH) in its Hospital Medical Records Management Manual. All the respondents have formally established medical records units that are manned, mostly, by individuals with records management training and headed by qualified, as prescribed by the manual, records officers. And in the creation, maintenance and disposal of records the respondents established standards and processes based on the guidelines provided by the DOH manual, as well as on pertinent laws.
But it was also discovered that the respondent medical records units are burdened by a severe lack of storage space and are hampered by the lack of standardized training programs for its medical records personnel. On the average, the respondent hospitals, lack 82.667 percent of their required storage space as given by the computations based on the average space required formula in the manual. Furthermore, the hospitals do not provide a standardized training for their records personnel; they mostly rely on the Records Management and Archives Office (RMAO) to provide such training.
The study recommends that a feasibility study was conducted using "activity based costing" in its cost benefit analysis in order to justify its urgent need to acquire additional storage space. Also, the study recommends that a standardized training program be established not just for those records personnel without records management backgrounds but also for those who have the requisite backgrounds but need to further their knowledge and update their technical skills.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Medical records -- Management -- Philippines -- Quezon City; Medical records -- Management -- Philippines -- Manila